1993
DOI: 10.1038/ng0193-62
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1 gene mutations in neuroblastoma

Abstract: The introduction of human chromosome 17 suppresses the tumourigenicity of a neuroblastoma cell line in the absence of any effects on in vitro growth and the neurofibromatosis type 1 (NF1) gene may be responsible. Here we report that 4 out of 10 human neuroblastoma lines express little or no neurofibromin and that two of these lines show evidence of NF1 mutations, providing further proof that NF1 mutations occur in tumours that are not commonly found in NF1 patients. We also show that NF1 deficient neuroblastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(54 citation statements)
references
References 28 publications
2
50
0
2
Order By: Relevance
“…An analogous observation with the two main mammalian p21-ras-GAPs, p120-GAP and neuro®bromin (neuro®bromatosis 1 gene product), has been made. In these studies, neuro®bromin expression was reduced or absent in several di erent tumor types, but no changes in p120-GAP expression were observed (Johnson et al, 1993;The et al, 1993).…”
mentioning
confidence: 70%
“…An analogous observation with the two main mammalian p21-ras-GAPs, p120-GAP and neuro®bromin (neuro®bromatosis 1 gene product), has been made. In these studies, neuro®bromin expression was reduced or absent in several di erent tumor types, but no changes in p120-GAP expression were observed (Johnson et al, 1993;The et al, 1993).…”
mentioning
confidence: 70%
“…Earlier studies on other malignancies have reported mutations of the NF1 gene leading to loss of gene expression. [7][8][9] The shortening of the cell cycle in poorly differentiated cancer cells could lead to diminution of primary transcripts from large genes such as NF1. However, this does not seem to be the case, eg, in RB gene expression in TCC, which is a large gene.…”
Section: Discussionmentioning
confidence: 99%
“…Three neuroblastoma cell lines (90-4, 90-6, 90-10SK-n-SH) were also used for our methylation studies (kindly provided by Dr Andre Bernards; The et al, 1993). Brie¯y, total RNA from several human neuroblastoma cell lines was assessed by blot analysis using a 5' NF1 cDNA probe, representing nucleotides 1748 to 2673 (Genbank accession number M89914).…”
Section: Methylation In the Human Nf1 Promoter Regionmentioning
confidence: 99%